Revisiting the Affect Regulation Model of Binge Eating: A Meta-Analysis of Studies using Ecological Momentary Assessment - Haedt-Matt, Alissa A. (2011)
The affect regulation model of binge eating, which posits that patients binge eat to reduce negative affect (NA), has received support from cross-sectional and laboratory-based studies. Ecological momentary assessment (EMA) involves momentary ratings and repeated assessments over time and is ideally suited to identify temporal antecedents and consequences of binge eating. This meta-analytic review includes EMA studies of affect and binge eating. Electronic database and manual searches produced 36 EMA studies with N = 968 participants (89% Caucasian women). Meta-analyses examined changes in affect before and after binge eating using within-subjects standardized mean gain effect sizes (ES). Results supported greater NA preceding binge eating relative to average affect (ES = .63) and affect before regular eating (ES = .68). However, NA increased further following binge episodes (ES = .50). Preliminary findings suggested that NA decreased following purging in Bulimia Nervosa (ES = −.46). Moderators included diagnosis (with significantly greater elevations of NA prior to bingeing in Binge Eating Disorder compared to Bulimia Nervosa) and binge definition (with significantly smaller elevations of NA before binge versus regular eating episodes for the DSM definition compared to lay definitions of binge eating). Overall, results fail to support the affect regulation model of binge eating and challenge reductions in NA as a maintenance factor for binge eating. However, limitations of this literature include unidimensional analyses of NA and inadequate examination of affect during binge eating as binge eating may regulate only specific facets of affect or may reduce NA only during the episode.